Tìm n, biết: ($\frac{2}{3}$)$^{-n+1}$ = ($\frac{3}{2}$)$^{3}$

Question

Tìm n, biết:
($\frac{2}{3}$)$^{-n+1}$ = ($\frac{3}{2}$)$^{3}$

in progress 0
Katherine 5 tháng 2021-07-13T08:56:26+00:00 2 Answers 2 views 0

Answers ( )

    0
    2021-07-13T08:57:43+00:00

    Đáp án:

    $n = 4$

    Giải thích các bước giải:

    $\begin{array}{l}\left(\dfrac{2}{3}\right)^{-n + 1}=\left(\dfrac{3}{2}\right)^3\\ \Leftrightarrow \left(\dfrac{2}{3}\right)^{-n + 1}=\left(\dfrac{2}{3}\right)^{-3}\\ \Leftrightarrow -n + 1 = -3\\ \Leftrightarrow n = 4 \end{array}$

    0
    2021-07-13T08:57:48+00:00

    Đáp án:

     

    Giải thích các bước giải:

     `(2/3)^(-n+1)=(3/2)^3=[(2/3)^(-1)]^3`

    `=>(2/3)^(-n+1)=(2/3)^(-3)`

    `=>-n+1=-3`

    `=>-n=-4`

    `=>n=4`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )